2012
DOI: 10.1089/jop.2011.0218
|View full text |Cite
|
Sign up to set email alerts
|

Diosmin Protects Rat Retina from Ischemia/Reperfusion Injury

Abstract: Diosmin protected the retina from I/R injury, possibly via a mechanism involving the regulation of oxidative parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Studies have presumed that oxidative stress is likely to be causally involved in IR-induced retinal damage [4,5]. Oxidative stress is defined as an increase over physiological values in the intracellular concentrations of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have presumed that oxidative stress is likely to be causally involved in IR-induced retinal damage [4,5]. Oxidative stress is defined as an increase over physiological values in the intracellular concentrations of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…It seems reasonable to consider the potential use of defined antioxidants in the treatment of retinal ischemia diseases. Tong et al [5] proved that diosmin markedly protected the retina from IR-induced injury by preventing the loss of retinal neurons and improving the oxidative parameters of the tissue, and a recent study also showed that several kinds of drugs with antioxidant properties significantly counteracted the negative effects induced by retinal ischemia [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [11], we found a neuroprotective effect of diosmin against retinal I/R injury. Furthermore, as a naturally occurring flavonoid glycoside, diosmin is a vascular protective agent used to treat chronic venous insufficiency [12], hemorrhoids, lymphedema, and varicose veins.…”
Section: Introductionmentioning
confidence: 75%
“…Rats were divided into two groups (n = 16/group): a physiological saline-treated group (Vehicle) and a 10 mg/kg diosmin-treated group (Diosmin). This dosage was chosen based on our previous study [11]. Animals were given physiological saline or diosmin intragastrically 30 min before the onset of ischemia, and then daily after I/R injury until sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…Это приводит к уменьшению высво-бождения воспалительных радикалов, простагландинов и тромбоксана. Антиоксидантные свойства, достигаются путѐм уменьшения количества свободных радикалов, оказывающих повреждающее действие на биологические мембраны, провоцируя развитие эндотелиальной дисфункции [64]. Известны следующие основные клинические эффекты микронизированной очищенной фракции флавоноидов: улучшение микроциркуляции: угнетение выработки молекул адгезии [65], препятствует адгезии лейкоцитов и / или их миграции, ингибирует образование свободных радикалов [66], макрофагов, тормозит синтез простагландина Е2 или F2 и тромбоксана В2 ингибирует увеличение микрососудистой проницаемости, индуцированной ишемией [67] и гистамин, брадикинин, лейкотриен В4 при ишемии либо реперфузии снижение апоптоза паренхиматозных клеток, ингибирует тромбоцитарную активность [68] (in vitro); лимфотропный: повышает сократимость лимфатических сосудов в лабораторных условиях [69], улучшает лимфатический дренаж [70], снижает концентрацию белка в ткани и фибробластов при лимфостазе [71].…”
unclassified